The cruise industry and the COVID-19 outbreak (2020)
The movement of cruise ships has the potential to be a major trigger of coronavirus disease (COVID-19) outbreaks. In Australia, the cruise ship Ruby Princess became the largest COVID-19 epicenter. When the Ruby Princess arrived at the Port of Sydney in New South Wales on March 19, 2020, approximately 2700 passengers disembarked. By March 24, about 130 had tested positive for COVID-19, and by March 27, the number had increased to 162. The purpose of this study is to analyze the relationship between the cruise industry and the COVID-19 outbreak. We take two perspectives: the first analysis focuses on the relationship between the estimated number of cruise passengers landing and the number of COVID-19 cases. We tracked the movement of all ocean cruise ships around the world using automatic identification system data from January to March 2020. We found that countries with arrival and departure ports and with ports that continued to accept cruise ships until March have a higher COVID-19 infection rate than countries that did not. The second analysis focuses on the characteristics of cruise ships infected with COVID-19. For this purpose, we utilize the list named “Cruise ships affected by COVID-19” released by the Centers for Disease Control and Prevention. As a result, cruise ships infected with COVID-19 were large in size and operated regular cruises that sailed from the same port of arrival and departure to the same ports of call on a weekly basis.